33=-3(21-b)+3(b-4)

Simple and best practice solution for 33=-3(21-b)+3(b-4) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 33=-3(21-b)+3(b-4) equation:


Simplifying
33 = -3(21 + -1b) + 3(b + -4)
33 = (21 * -3 + -1b * -3) + 3(b + -4)
33 = (-63 + 3b) + 3(b + -4)

Reorder the terms:
33 = -63 + 3b + 3(-4 + b)
33 = -63 + 3b + (-4 * 3 + b * 3)
33 = -63 + 3b + (-12 + 3b)

Reorder the terms:
33 = -63 + -12 + 3b + 3b

Combine like terms: -63 + -12 = -75
33 = -75 + 3b + 3b

Combine like terms: 3b + 3b = 6b
33 = -75 + 6b

Solving
33 = -75 + 6b

Solving for variable 'b'.

Move all terms containing b to the left, all other terms to the right.

Add '-6b' to each side of the equation.
33 + -6b = -75 + 6b + -6b

Combine like terms: 6b + -6b = 0
33 + -6b = -75 + 0
33 + -6b = -75

Add '-33' to each side of the equation.
33 + -33 + -6b = -75 + -33

Combine like terms: 33 + -33 = 0
0 + -6b = -75 + -33
-6b = -75 + -33

Combine like terms: -75 + -33 = -108
-6b = -108

Divide each side by '-6'.
b = 18

Simplifying
b = 18

See similar equations:

| 1/3•28.26•10 | | 5Xm=30 | | 2x/3-7x/8+5x/18+x/24=4/9 | | 4/n=8/10 | | 2x+y(12+x)=-4 | | x/4=(x/5)-1 | | .5t+8=2t-16-.5t | | 3/12=n/24 | | 24=-3(21-b)+2(b-4) | | 1.5t+8=2t-16-.5t | | 20x+18=-7 | | F/1.2=3.2 | | 2x/3-5/6=x/4 | | 24y+8w+12x= | | N/24=1/12 | | 19-2(x+3y)-2x= | | 0x+15y=75 | | N/21=1/12 | | -3(x+8)=18+3x | | 6x+7x-3x=64 | | givenf(x)=x^3 | | 4w-20= | | 2/5x=5/6 | | 3/n=1/8 | | 8s-10=10 | | 3x^2=7x-2x | | 6-(x+4)+3x=8x-2(3x+4) | | 3b/4=3/2 | | N/21=1/7 | | 2/3=1/1=f | | 2/8=n/32 | | s+5=4 |

Equations solver categories